(untitled) (Al-Academy, 2023)
The research aims to (identify the applications of pedagogy in art education), the research community included, art education for the primary stage, so the community consisted of (8) main areas in art education, either the research sample was chosen, two main areas (objectives, and content), and included the research methodology (descriptive and analytical), the researcher built the research tool represented (the validity form of the tool) and presented to a group of experts to indicate its validity as well as to measure its stability, To show the results, the researcher used the percentage, and the researcher recommended - modifying the curriculum every period of time, such as every four years, others.